Long wavelength infrared quantum cascade detector with a broadband response. (14th August 2018) - Li, Liang; Zhou, Xiaohao; Tang, Zhou; Zhou, Yuwei; Zheng, Yuanliao; Li, Ning; Chen, Pingping; Li, Zhifeng; Lu, Wei
Abstract: A novel structure to achieve long wavelength infrared broadband detection ranging from 7.6–10.4 µ m is proposed via quantum cascade detector. With a pair of identical coupled quantum wells separated by a thin barrier, acting as absorption regions, the relative linewidth (Δ E / E ) of response can be dramatically broadened to 30.7%. Moreover, this structure introduces about 30% enhancement in blackbody responsivity. It is shown that the spectral shape can be tuned by the bias voltage effectively, while it is insensitive to the working temperature. The device can work at liquid nitrogen temperature with Johnson noise limited blackbody detectivity of 5.4  ×  10 8 Jones.